2015
DOI: 10.1080/87559129.2015.1057839
|View full text |Cite
|
Sign up to set email alerts
|

Include mushroom in daily diet—A strategy for better hepatic health

Abstract: Liver, the most important metabolic organ of the body is also the major organ for the detoxification of the blood stream. If the accumulation of toxins is faster than their removal by liver, hepatic damage occurs. Although synthetic drugs are available in the market, long term use of such drugs has consequential side effects. Therefore, the growing need to find safe, costeffective drugs devoid of adverse effects is spawning extensive research. Mushrooms are rising as a major medicinal food and pharmaceuticals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 118 publications
0
12
0
Order By: Relevance
“…Therefore, extensive research is needed to find safe and cost effective drug. 63 Recently, Sun et al (2014) isolated eburicoic acid and trametenolic acid B from L. sulphureus and evaluated their hepatoprotective activity using Sprague-Dawley rats. They made hepatic fibrosis models induced by CCl 4 and evaluated content of AST and ALT, levels of liver cell injury and degree of liver fibrosis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Therefore, extensive research is needed to find safe and cost effective drug. 63 Recently, Sun et al (2014) isolated eburicoic acid and trametenolic acid B from L. sulphureus and evaluated their hepatoprotective activity using Sprague-Dawley rats. They made hepatic fibrosis models induced by CCl 4 and evaluated content of AST and ALT, levels of liver cell injury and degree of liver fibrosis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…R. Heim; Termitomyces medius R. Heim & Grassé etc. (Khatua et al 2013(Khatua et al , 2015Chatterjee and Acharya 2015;Patra et al 2012). Macrocybe gigantea (Massee) Pegler & Lodge is also a medicinally potent edible mushroom which is common to West Bengal in rainy season.…”
Section: Introductionmentioning
confidence: 99%
“…Liver damage being a global disorder usually caused by oxidative stress, 75 alcohol, carbon tetrachloride, galactosamine, paracetamol; chemotherapeutic agents and antitubercular drugs are causing hepatotoxicity and severe liver damage. 76,77 Throughout the world, studies have revealed that natural antioxidants may function in curing certain hepatic damages.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…78 Hepatoprotective properties have also been reported for mushroom extracts and mushroom-derived molecules. 75 Current studies of revealed the hepatoprotective action of the ethanolic extract of A. hygrometricus against CCl 4 induced chronic hepatotoxicity in animal model. Results indicated that antioxidants present in the extract might terminate the chain reaction cascade of CCl 4 intoxication by scavenging the intermediates free radicals.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%